2010
DOI: 10.4102/jsava.v81i1.88
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against GnRH may suppress aggressive behaviour and musth in African elephant (Loxodonta africana) bulls - a pilot study

Abstract: Aggressive behaviour and musth are constant problems in captive and sometimes in free-ranging African elephant bulls. Aggressive bulls are difficult and musth bulls almost impossible to manage without severely restricting their movement either by leg-chaining or using tranquillisers. This study investigated the relationship between faecal androgen metabolites (FAM) and faecal cortisol metabolites (FCM) concentrations and aggressive behaviour and tested a GnRH vaccine as a means of down-regulating aggressive be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 36 publications
2
34
0
Order By: Relevance
“…17,19,20,40,41,48,54 Preliminary evaluation of a GnRH vaccine for control of aggression and musth behavior in bull elephants has shown some degree of variation in the response of individuals, and this phenomenon has been noted in a variety of other species. 2,13,23,30,32,52 More work clearly is needed to optimize the dose and frequency of vaccination when using the Repro-BLOC formulation in elephants, because it took more than a year for the effects to be realized. It is not clear why this elephant required multiple boosters before the desired effect of vaccination occurred.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,19,20,40,41,48,54 Preliminary evaluation of a GnRH vaccine for control of aggression and musth behavior in bull elephants has shown some degree of variation in the response of individuals, and this phenomenon has been noted in a variety of other species. 2,13,23,30,32,52 More work clearly is needed to optimize the dose and frequency of vaccination when using the Repro-BLOC formulation in elephants, because it took more than a year for the effects to be realized. It is not clear why this elephant required multiple boosters before the desired effect of vaccination occurred.…”
Section: Discussionmentioning
confidence: 99%
“…3,18,30,36,41,43 In elephant bulls, GnRH vaccination has shown efficacy in suppressing testosterone production and musth behaviors, presumably by similarly inhibiting pituitary control of gonadal steroidogenic activity. 2,13,14 A carefully managed contraception strategy would be of particular value in areas of high elephant density in close proximity to humans to mitigate human-elephant conflicts and in game parks where protected space and resources are limited. It would be beneficial to compare the efficacy, duration of effect, reversibility, longterm health and genetic effects, and social and behavioral effects of GnRH vaccination in elephants with those of porcine zona pellucida vaccination, which prevents fertilization by blocking sperm binding to the egg and is currently used in female elephants for contraception.…”
Section: Discussionmentioning
confidence: 99%
“…For African elephants in zoos as well as in the wild, these methods have been shown to be practical and enable long-term monitoring of environmental and social factors impacting on adrenocortical activity without interfering with the result (Ganswindt et al 2005a,b, Rasmussen et al 2008, Ganswindt et al 2010. In this regard, several studies demonstrated that extrinsic and intrinsic factors like translocation, seasonal variation, intra-group competition or sexual state can affect glucocorticoid levels in African elephants (Foley et al 2001, Ganswindt et al 2005a,b, Viljoen et al 2008a,b, Ganswindt et al 2010, De Nys et al 2010. For various reasons, the relationship between adrenal activity and physical injuries is less documented.…”
mentioning
confidence: 99%
“…Castration is not limited to use in livestock species, but also finds application in companion animals, horses maintained for recreational purposes, and, more recently, wildlife (De Nys et al, 2010). The typical purpose of castration is to ease handling and management by controlling sexual and aggressive behaviour.…”
Section: Motivation For Castrationmentioning
confidence: 99%
“…Immunocastration was used in both stallions and mares (Garza et al, 1988) to suppress reproduction, with the first successful report of its use in stallions (Schanbacher & Pratt, 1985). Immunocastration also showed promise to control aggressive behaviour in wild and captive African elephants by successfully decreasing androgen production (De Nys et al, 2010). Research into immunocastration of primates indicated that an increased GnRH-antibody titre and decreased testosterone production were associated with a reduced prostate weight (Giri et al, 1991).…”
Section: Non-livestock Speciesmentioning
confidence: 99%